How aggregate electricity demand responds to hourly wholesale price fluctuations - Lion Hirth; Tarun Khanna; Oliver Ruhnau (ZBW - Leibniz Information Centre for Economics, 2023)
Electricity needs to be consumed at the very moment of production, leading wholesale prices to fluctuate widely at (sub-)hourly time scales. This article investigates the response of aggregate electricity demand to such price variations. Using wind energy as an instrument, we estimate a significant and robust short-term price elasticity of about -0.05 in Germany and attribute this to industrial consumers. While seemingly modest, our results imply that even with limited exposure to real time prices, short-term demand response facilitates decarbonization of the electricity grid by reducing the need for battery storage or backup fossil power by approximately 8%.
Older version: http://hdl.handle.net/10419/249570
Keywords: Q41; Q42; 330; Short-term price elasticity; Electricity markets; Demand response; Instrumental variables; Wind energy